2008
DOI: 10.1176/ps.2008.59.6.655
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs of Families of Adults With Mental Illness and Preferences Regarding Family Services

Abstract: The needs and preferences of family members of adults with mental illness are diverse and varied. Consequently, these families may benefit from ongoing provision of information and support tailored to meet the families' individual needs. Continued efforts should be made to understand and address consumer and family needs, potential barriers to participation in family services, and the relationship between stigma and family need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 34 publications
4
22
1
6
Order By: Relevance
“…Family members play important roles in the lives of adults with serious mental illnesses (SMI) (1), and often seek information and support regarding treatments, relevant resources, coping, communication and problem solving skills (2)(3)(4)(5)(6). While virtually all reviews recommend including families in the care of persons with mental illness (7), reported rates rarely exceed 50% (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Family members play important roles in the lives of adults with serious mental illnesses (SMI) (1), and often seek information and support regarding treatments, relevant resources, coping, communication and problem solving skills (2)(3)(4)(5)(6). While virtually all reviews recommend including families in the care of persons with mental illness (7), reported rates rarely exceed 50% (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Eight studies included barriers that were addressed by persons with SMI [1824]. Eleven studies reported barriers that were addressed from the family perspective [21, 22, 2432]. Twenty-five studies reported on barriers experienced by professionals [14, 19, 21, 22, 2426, 33–50].…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies reported only the perspectives of professionals [3336, 3841, 44–50]. Five studies reported only the perspectives of family [27, 2932] and two studies reported only on the perspectives of persons with SMI [18, 20]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is plenty of evidence to support the value of education for families of individuals living with mental illness (Bertrando, 2006;Drapalski, et al, 2008;Hatfield, 1990;Johnson, 2005;Jones, 2005;Marsh & Johnson, 1997;Moore, 2005;O'Connell, 2006;Sherman, 2003). BC's mental health reform best practices recognizes that "training in coping skills, communication, information and support reduces the level of crisis in families, as well as reducing the relapse rate of the patient" (Ministry of Health, 2000, p.…”
Section: List Ofmentioning
confidence: 99%